(untitled) (JOURNAL OF ADVANCES IN CHEMISTRY, 2017)
27 liquid-liquid extraction-chromogenic systems containing Mo(VI), o-hydroxythiophenol derivative HTPDs: 2-hydroxy-5-chlorothiophenol (HCTP), 2-hydroxy-5-bromothiophenol (HBTP) or 2-hydroxy-5-iodothiophenol (HITP) and aromatic amine (AA) were studied. Aniline (An), N-methylaniline (mAn), N,N-dimethylaniline (dAn), o-toluidine (o-Tol), m-toluidine (m-Tol), p-toluidine (p-Tol), 3,4-xylidine (o-Xyl), 2,4-xylidine (m-Xyl), and 2,5-xylidine (p-Xyl) were the examined AAs. Optimization experiments for molybdenum extraction-spectrophotometric determination were performed and the following parameters were found for each of the systems: organic solvent (opt), pH (opt), CHTPD (opt), CAA (opt), shaking time (opt), l (max) and e (max). Under the optimum conditions, the molar ratio of the reacting Mo(V), HTPD and AA was 1:2:2 and the degrees of Mo extraction were R³98.4%. Linear relationships involving the spectral characteristics of the extracted complexes (lmax or emax) and some fundamental properties of the halogen substituent in the HTPD were discussed. The effect of foreign ions was examined and two sensitive, selective and precise procedures for extraction-spectrophotometric determination of molybdenum were proposed. The relative standard deviations for Mo content of (3-5)´10–4 mass % were 4% (HCTP-An procedure) and 3% (HBTP-An procedure).